Transcriptomic Analysis of the Onchidium reevesii Central Nervous System in Response to Cadmium - Gu, Bingning; Yang, Tiezhu; Liu, Xin; Shen, Heding (Frontiers in Marine Science, 2019)
Shellfish are widely used in coastal environments for biomonitoring of heavy metal pollution. Research on the sea slug Onchidium reevesii, an economically important benthic gastropod, is limited due to a lack of genomic resources. This study, based on Illumina sequencing, compared the transcriptomes of O. reevesii before and after cadmium exposure, and used time-series expression analysis. The molecular level stress response mechanism operating in this organism in environmental stress conditions was investigated. De novo assembly of the O. reevesii transcriptome yielded 51,007 unigenes, of which 14,774 were annotated. Time-series expression analyses resulted in clustering of most responsive transcripts into 16 statistically significant expression profiles. Gene Ontology (GO) enrichment analysis based on time-series expression identified metal ion binding, synaptic transmission, and oxidative stress as important biological processes, and expression analysis identified genes related to invertebrate responses to environmental stress. Furthermore, we have generated the first transcriptome of O. reevesii, and the extensive sequence data produced will provide valuable molecular resources for study of the response of O. reevesii to cadmium exposure.